The tavern : a social history of drinking and conviviality - Barleen, Steven (Steven D.) (History of human spaces., 2019)
"Since the first Europeans settled in North America, much of American life and politics have happened around the tavern. Readers of all kinds will appreciate this in-depth analysis of the tavern and its influence on American life and society throughout history"--